The chemical topology of a bacterial swarm - Garg, Neha (J Biol Chem, 2018)
Microbes respond to antibiotics by initiating a suite of defense mechanisms, including the production of small-molecule effectors. However, it is not well-known how these defenses vary according to the particular effector or antibiotic and bacterial state, due in part to the challenges of monitoring small molecules in complex environments. A new study uses state-of-the-art imaging techniques to track the location of secreted small molecules produced by a bacterial swarm in response to different antibiotics, providing unexpected insights into the spatial heterogeneity of bacterial stress responses.